Validation of the Psychometric Properties of the Practice Environment Scale of Nursing Work Index (PES-NWI) Questionnaire in the Context of Kenya's Nursing Organizational Work Culture - Evans Kasmai Kiptulon; Mohammed Elmadani; Godfrey Mbaabu Limungi; Anna Szőllősi; Dahabo Adi Galgalo; Peter Murage; Pauline Okari; Orsolya Maté; Adrienn Ujváriné Siket (Elsevier, 2024)
Background: The global shortage of nurses is posing a significant threat to the provision and sustainability of quality health care services worldwide. The importance of nursing organizational culture and validated tools to accurately measure it, is of paramount importance in mitigation of this shortage, especially in Low- and middle-income-countries like Kenya. Methodology: This was a cross-sectional online validation survey among 212 nursing personnel working in various healthcare facilities across Kenya. The aim of the study was to assess the validity and reliability of the psychometric properties of the Practice Environment Scale of Nursing Work Index within the framework of nursing organizational culture in Kenya and determine how Kenyan nurses rate their organizational culture. Data was analyzed using SPSS version 28. Cronbach's alpha was used to determine reliability while Exploratory Factor Analysis and Confirmatory Factor Analysis were used to test validity. Results: The 5-structure of Lake's PES-NWI was unsupported by confirmatory factor analysis and a new 7-Factor Kenyan PES-NWI version was created. The new tool was reliable and with acceptable fit. Participants showed a mixed rating of their organizational culture with overall organizational culture largely rated neutral (M = 2.51, SD = 1.01). Conclusion: The Kenyan PES-NWI is a valid and reliable tool that could be used to assess organizational culture. The study highlighted the critical need to further develop context-specific tools to accurately measure nursing organizational culture work environments particularly in Low and-Middle-Income countries like Kenya facing significant nursing shortages. As nursing becomes increasingly dynamic and complex, it is essential for nursing and healthcare researchers to re-validate research tools to continuously improve them.